Marriage is definitely made in heaven: a phenomenological study on the marital satisfaction of Indian Muslim women - Arshad, Munira; Islam, Arshad (IIUM Press, International Islamic University Malaysia, 2017)
The purpose of this phenomenological study was to explore the lived experience of Indian Muslim women regarding their marital satisfaction and to understand the perceived quality of their relationships. This qualitative study is the first of its kind to consider marital satisfaction among Indian Muslim women. A semi-structured interview questions reflecting the four research questions were formulated to use in face-to-face in-depth interview among the six Indian Muslim women from Mumbai, India. The study analyzed the relevant constructed meanings that emerged from all interviews and clustered them into nine main themes with 19 sub-themes in an attempt to reach an in-depth understanding of the lived marital experiences of the Indian Muslim woman.